1997
DOI: 10.1002/bbpc.19971010604
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic 15N NMR study of kinetic hydrogen/deuterium isotope and tunnel effects on the triple proton transfer in crystalline 3,5‐dimethylpyrazole

Abstract: Using dynamic solid state I5N CPMAS NMR spectroscopy (CP=cross polarization, MASSmagic angle spinning) the kinetics of the degenerate intermolecular triple proton and deuteron transfer in the cyclic trimers of "N-labeled polycrystalline 3,s-dimethylpyrazole (DMP) have been studied in a wide temperature range. At high temperatures, rate constants of the various isotopic HHH, HHD, HDD, and DDD transfer reactions are obtained in the millisecond timescale by lineshape analysis of partially deuterated doubly I5N-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 57 publications
2
36
0
Order By: Relevance
“…Many of the solid-state systems studied by Limbach's group in Berlin [85][86][87][88][89][90][91][92][93][94][95] have been complexes containing N-HÁ Á ÁN hydrogen bonds with proton transfer rates which are many orders of magnitude slower than those in benzoic acid. The characteristic rate constants are on a timescale similar to 15 N chemical shift interactions so the proton transfer motions are revealed in the evolution of the 15 N NMR lineshapes with temperature; these are the classic effects of chemical exchange on the NMR spectrum.…”
Section: Multiple Hydrogen Transfer Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the solid-state systems studied by Limbach's group in Berlin [85][86][87][88][89][90][91][92][93][94][95] have been complexes containing N-HÁ Á ÁN hydrogen bonds with proton transfer rates which are many orders of magnitude slower than those in benzoic acid. The characteristic rate constants are on a timescale similar to 15 N chemical shift interactions so the proton transfer motions are revealed in the evolution of the 15 N NMR lineshapes with temperature; these are the classic effects of chemical exchange on the NMR spectrum.…”
Section: Multiple Hydrogen Transfer Reactionsmentioning
confidence: 99%
“…One such investigation concerns the cyclic trimer of 3,5-dimethylpyrazole [85,94] for which the 15 N CPMAS NMR spectra have been recorded as a function of temperature. There are three mobile hydrogen atoms and using lineshape analysis with chemical exchange good agreement has been obtained with simulated spectra from which the rate constants for the proton transfer have been extracted.…”
Section: Multiple Hydrogen Transfer Reactionsmentioning
confidence: 99%
“…Multiple proton transfers in solid pyrazole dimers, trimers and tetramers ( Fig. 1e to 1g) are slower and have been studied by 15 N NMR magnetization transfer and line shape analysis [23][24][25][26][27][28][29][30][31]. The fastest process in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Spiess et al [33] have shown by two-dimensional rotor-synchronized 13 C NMR that a very slow tautomerism Hydrogen bonded systems exhibiting multiple proton transfers in the solid state. a N, N -diphenyl-6-aminofulvene-1-aldimine [19], b tropolone [32,33], c benzoic acid dimer [13][14][15], d arylamidine dimer [21,22], e pyrazole dimer, f pyrazole trimer and g pyrazole tetramer [24][25][26][27][28][29][30]. of solid tropolone observed by Bax et al [34] is associated with molecular jumps into neighboring vacant molecular sites.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazoles and particularly 3,5-dimethylpyrazole (1), show a dynamic process in the solid state that consists in the transfer, generally concerted, of several protons between the nitrogen atoms [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. This process (named SSPT, Solid State Proton Transfer) is illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%